Write head field design for correcting transition curvature in heat assisted magnetic recording - Jian-Gang (Jimmy) Zhu; Hai Li (AIP Advances, 2017)
In this paper, we present a method for correcting transition curvature in heat assisted magnetic recording. By appropriately varying the recording head field across the track width, straight transitions free of curvature can be created even with a circular thermal profile. Micromagnetic modeling study has been performed to show the consequent signal-to-noise ratio enhancement and corresponding area density gain. Effect of less-than-optimum head field has been analyzed.